Patient-reported outcomes with medical management of benign prostatic hyperplasia: a prospective study in a tertiary care teaching hospital of rural West Bengal, India - Mandal, Soumitra; Mandal, Ananya; Majhi, Tapas K.; Mandal, Sonai; Gangopadhyay, Tanmoy; Das, Asoke K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Effectiveness of pharmacotherapy in benign prostatic hyperplasia (BPH) is generally evaluated by clinical measures. Outcome of the treatment from the patient’s perspective however cannot be evaluated which may result communication gap between the patient and the physician. Patient-Reported Outcomes (PRO) studies can bridge this gap. This study was undertaken to evaluate outcomes and to assess the impact of medical management of BPH on general health-related quality of life. Methods: In this prospective, observational study, eligible patients with BPH attending a Urology clinic in a tertiary care rural hospital of West Bengal were enrolled and followed up on third and sixth months from baseline. Symptom assessment of BPH were assessed through International Prostate Symptom Score (I-PSS), BPH Impact Index (BII) and Health Related Quality of life questionnaires. Tools of descriptive statistics were used for analysis of data. Results: In the study population of 66 patients, 50% were treated with monotherapy (alpha blockers) and 50% were treated with combinations (alpha blocker and 5alpha reductase inhibitors). After 6 months of medical management, I-PSS was decreased from 18.86±5.53 to 11.76±3.94 (p <0.001), BII score decreased from 9.65±2.59 to 5.89±2.24 (p <0.001) and VAS score increased from 51.44±10.03 to 54.24±11.38 (p <0.001). Conclusions: We found medical management definitely improved quality of life in BPH patients and significantly decreased symptoms. This study is a step in the direction of development of larger and longer term PRO studies in BPH management.